Culture, society, and development in India : essays for Amiya Kumar Bagchi - Bagchi, Amiya Kumar; Ghosh, Arunabha; Sanyal, Manoj Kumar (Orient BlackSwan, 2009)
Festschrift on Amiya Kumar Bagchi, b. 1936, Indian economist and historian; contributed articles.